Modelowanie charakterystyk przetwornicy buck z monolity cznym regulatorem LT1073 w programie SPICE - Posobkiewicz, Krzysztof; Gorecki, Krzysztof; Zargbski, Janusz (Видавництво Національного університету «Львівська політехніка», 2003)
In the paper a new electrothermal model of LT1073 pulse regulator is presented and tested. This model has been implemented in SPICE and SwitcherCAD tools. The BUCK dc-dc chopper comprising LT1073 has been investigated. The results of measurements as well as simulations by SPICE and SwitcherCAD are presented and compared.